Joint‐Preserving Surgery for Talar Malunions or Nonuions. Issue 1 (February 2017) - Chen, Gang; Hu, Mu; Xu, Yang; Zhen, Yue‐huan; Hong, Yuan; Xu, Xiang‐yang
Abstract : Objective: To describe the technique and analyze the outcomes of joint‐preserving surgical treatments which included anatomical reconstruction or alignment correction for talar malunions or nonunions, and avoid development of degenerative changes in the adjacent joints. Methods: Eight patients who had painful talar malunions or nonunions treated between 2009 and 2015 were included in this retrospective study. The mean age of the patients was 35.6 years, with patients aged from 18 to 58 years. Two patients had talar neck fractures and six had talar body fractures. According to a classification of post‐traumatic talar deformities, five patients were classified as type I (malunion and/or residual joint displacement), two as type II (nonunion with displacement), and one as type III (malunion with partial avascular necrosis [AVN]). Of these patients, six cases were treated with an osteotomy through the malunited fracture or removal of the pseudarthrosis, and two cases were corrected by supramalleolar or calcaneal osteotomies owing to complete disappearance of the former fracture lines. The follow‐up evaluation methods included the 36‐Item Short Form Health Survey (SF‐36) score, the American Orthopaedic Foot and Ankle Society (AOFAS) score, range of motion (ROM), and radiological analysis. The differences between postoperative scores and preoperative scores were evaluated statistically with the paired Student's t ‐test. Significance was assumed at P < 0.05. Results: The mean follow‐up time was 25.6 months. No wound healing problems or infections were observed. Solid union was obtained without redislocation in all cases, and with no signs of development or progression of AVN. At a mean of 25.6 months (range, 16–36 months) after reconstruction, all patients were satisfied with the result. The mean AOFAS score increased from 30.0 ± 7.0 pre‐operatively to 86.5 ± 7.8 post‐operatively ( P < 0.001), the mean SF‐36 score increased from 38.8 ± 4.1 to 81.4 ± 7.7 ( P < 0.001), and the average ROM (tibiotalar joint) increased from 40.5° ± 8.7° to 43.9° ± 7.2° ( P < 0.05). Discussion: Joint‐preserving procedures for talar malunions or nonunions can bring about satisfactory outcomes, and the appropriate procedure should be adopted according to different types of post‐traumatic deformities.